Utilization of Jack Fruit Pulp in Kalamae - Pomasa, Panjit; Thongprem, Nichapa; Takeungwongtrakul, Sirima; Kaewthong, Pensiri (Burapha Science Journal, 2026)
This research aimed to develop the formulation of Kalamae supplemented with jackfruit pulp to enhance the nutritional value. The different levels of jackfruit pulp (0, 10, 15, 20 and 25%, (w/w)) in Kalamae were studied. It was found that the use of 15% (w/w) jackfruit pulp in Kalamae had the highest overall liking scores by consumer test and liking score was like very much (p<0.05). The nutritive values including protein, fiber, moisture, and ash contents of Kalamae supplemented with jackfruit pulp at 15% (w/w) were higher than those without jackfruit pulp (p<0.05). Kalamae supplemented with jackfruit pulp at 15% (w/w) showed the lower carbohydrate and lipid contents, compared with those without jackfruit pulp (p< 0.05). Additionally, the selected Kalamae supplemented with jackfruit pulp at 15% (w/w), stored at 30±2 °C for 14 days, had microbiological quality as Thai community product standard (873/2016).